Um estudo sobre instrumentos de participação social na formulação da política habitacional do município de Santa Rosa - Leschko, Mauro André (2019)
The dissertation brings as a topic the exercise of civil society in the public sphere, using social participation instruments made available by Santa Rosa Municipality or produced by the civil society, at the field of municipal public housing policies formulation. It aims to identify the way civil society performs the formulation of public housing policies in Santa Rosa Municipality, managing urbanization and civil society issues, raising what the tools made available by the city council and by the executive power to formulate a development and housing policy for the Santa Rosa Municipality were. The public housing policy goes through the approvals of the master plan by Santa Rosa Municipality after the cities statute goes into force. The qualitative survey about this topic was bibliographical and documentary, being used mainly the existing documents at the executive and legislative power of Santa Rosa Municipality which bring the projects of the 2016 and 2017 master plans. The survey resulted in the explanation of the processing of the master plans, the identification of civil society representation and the formation of a civil society and the way the civil society segment action took place. It pointed of public housing policy issue and the local housing plan and social concern. The dissertation showed that the participation instruments availability is not embrancing enough and that public audictions should be better used by the civil society.